Merrill Moore papers - Moore, Merrill, 1903-1957.; Murray, Henry A. (Henry Alexander), 1893-1988.
Correspondence, diaries, literary papers, notebooks, biographical material, family papers, genealogical records, scrapbooks, printed matter, and other papers relating to Moore's career as a psychiatrist and poet. Documents his medical career at institutions including Boston City Hospital and Washingtonian Hospital (Boston, Mass.) as well as his years in private practice in Boston, Mass. Moore's literary papers consist chiefly of manuscript, typewritten, and printed sonnets supplemented by poems, prose writings, published articles and books, and other materials.
Subjects include Moore's research in mental illness and neurological disease chiefly in the areas of alcoholism, drug addiction, suicide, and syphilis; role as a consultant with companies producing bromides; and efforts to aid Jewish doctors to escape Nazi Germany, 1938-1940. Subjects also include Moore's World War II service as a U.S. Army medical officer in New Zealand and the South Pacific; studies of alcoholism and shell shock among military personnel; work to improve neurological services in military hospitals; tour of duty in China, 1946; and concern for friends who remained in China. Includes interviews with Moore and research materials collected by Henry A. Murray for a project at the Harvard Psychological Clinic.
Correspondents include Adam G.N. Moore and other family members. Other correspondents include Alexandra Adler, Arlie V. Bock, Stanley Cobb, Walter Ames Compton, Donald Davidson, Dudley Fitts, Winfred Overholser, John Crowe Ransom, Hanns Sachs, Harry C. Solomon, Allen Tate, Louis Untermeyer, and Frederic Lyman Wells.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Psychiatrist and poet. Full name: Austin Merrill Moore.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index of selected correspondents available in the Library of Congress Manuscript Reading Room and at
Keywords: Adler, Alexandra, -- 1901- -- Correspondence; Bock, Arlie V. -- 1888- -- Correspondence; Cobb, Stanley, -- 1887-1968 -- Correspondence; Davidson, Donald, -- 1893-1968 -- Correspondence; Fitts, Dudley, -- 1903-1968 -- Correspondence; Moore, Adam G. N. -- Correspondence; Overholser, Winfred, -- 1892-1964 -- Correspondence; Ransom, John Crowe, -- 1888-1974 -- Correspondence; Sachs, Hanns, -- 1881-1947 -- Correspondence; Solomon, Harry C. -- 1889-1982 -- Correspondence; Tate, Allen, -- 1899-1979 -- Correspondence; Untermeyer, Louis, -- 1885-1977 -- Correspondence; Wells, Frederic Lyman, -- 1884- -- Correspondence; Moore family; United States. -- Army -- Medical care; Boston City Hospital; Harvard University. -- Harvard Psychological Clinic; Washingtonian Hospital (Boston, Mass.); Alcoholism; American literature; American poetry; Americans -- China; Bromides; Drug abuse; Jews -- Germany; Literature; Medicine -- Practice -- Massachusetts -- Boston; Military psychiatry; Neurology; Poetry; Psychiatry; Sonnets, American; Suicide; Syphilis; War -- Psychological aspects; World War, 1939-1945 -- Medical care; World War, 1939-1945 -- Germany; World War, 1939-1945 -- New Zealand; World War, 1939-1945 -- Oceania; Poets; Psychiatrists